Determination of Optimum Conditions for Human Epithelial Type-2 Cell Culture and Fixation on Slides - Arshad, Muhammad Zain; Dawood Ahmad; Tanveer, Ayesha; Ribqa Akhtar; Yumna Rubab; Maryam Irtash (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine optimum conditions for Human Epithelial Type-2 (HEp-2) cell culture and fixation on slides.Study Design: Cross-sectional study.Place and Duration of Study: Department of Immunology, Armed Forces Institute of Pathology Rawalpindi, Pakistan from Apr to Sep 2022.Methodology: Study involved procuring viable HEp-2 cell suspension having different counts and sub-culturing on Teflon coated glass and synthetic plastic slides. Few slides were kept in CO2 incubator and other in normal incubator at varied temperatures. Half of slides were enriched with 10 % Hepes Minimum Essential Medium (HMEM) at timely intervals. Subsequently, slides from each group were fixed using 4 different fixation protocols for different durations and temperatures. After fixation, slides showing better cell growth on microscopy were stored at different temperature wrapped in aluminium foil. Following optimization, staining of slides with 305 known control samples for antinuclear antibodies (ANA) was done. Periodic microscopy was performed by two experienced observers working independently, and observations were noted.Results: It is better to subculture HEp-2 cells on synthetic plastic slides using viable suspension of four hundred thousand cells per ml and subsequently enrich by 10% HMEM at 90 minutes and 12 hours. Growth is optimal on slides kept at 5% CO2 incubation. For ANA detection fixation of cells at 24 hours with ice-cold methanol for 15 minutes is necessary and then slides can be stained or stored at -60 ºC upto 60 days.Conclusion: HEp-2 cells can be cultured on synthetic plastic slides and subsequently fixed using methanol.